Therapeutic applications of CRISPR/Cas9 mediated targeted gene editing in acute lymphoblastic leukemia: current perspectives, future challenges, and clinical implications - Assis, Alan Jhones Barbosa; Santana, Brunna Letícia de Oliveira; Gualberto, Ana Cristina Moura; Pittella-Silva, Fabio (Frontiers in Pharmacology, 2023)
Acute Lymphoblastic Leukemia (ALL) is the predominant hematological malignancy in pediatric populations, originating from B-or T-cell precursors within the bone marrow. The disease exhibits a high degree of heterogeneity, both at the molecular level and in terms of clinical presentation. A complex interplay between inherited and acquired genetic alterations contributes to disease pathogenesis, often resulting in the disruption of cellular functions integral to the leukemogenic process. The advent of CRISPR/Cas9 as a gene editing tool has revolutionized biological research, underscoring its potential to modify specific genomic loci implicated in cancer. Enhanced understanding of molecular alterations in ALL has facilitated significant advancements in therapeutic strategies. In this review, we scrutinize the application of CRISPR/Cas9 as a tool for identifying genetic targets to improve therapy, circumvent drug resistance, and facilitate CAR-T cell-based immunotherapy. Additionally, we discuss the challenges and future prospects of CRISPR/Cas9 applications in ALL.